Tingkat Kecemasan dan Perilaku Protokol Kesehatan pada Mahasiswa di Pulau Jawa pada Masa Pandemi Covid-19 - Puji Laksmini; Andi Eka Yunianto; Andy Muharry (HB PRESS, 2021)
COVID-19 pandemic has made many changes in various orders and layers in society, either in economic field, social field, or physical and mental health. Mental disorders also occurred among students. Apart from the COVID-19 disease, students also faced new learning situations, where most of them used online methods. This study aimed to determine the students’ anxiety levels and health protocol behavior and to analyze the relationship between these two variables. This study used a quantitative analysis with a cross-sectional study design involving 2014 students in Java. The results showed that 52,9% of students had a high anxiety level and most of them (52,8%) showed low health protocol behavior. There was a significant relationship between anxiety levels and health protocol behavior (p=0,0001; OR=1,55; 95% CI=1,30-1,85) meaning that respondents with a low anxiety level tended to have 1,55 times higher risk performing poor health protocol behavior than those with a high anxiety level.